Effects of social networking sites usage on Chinese students life satisfaction in Malaysia: cultural identity as a mediator - Zhao, Wenwen; Osman, Mohd Nizam; Omar, Siti Zobidah; Yaakup, Hani Salwah (Universiti Putra Malaysia Press, 2023)
ocial networking sites (SNSs) serve as a powerful tool for international students to adapt to the host country and improve life satisfaction. However, the use of SNSs also brings negative influences on their life satisfaction. Additionally, the mechanisms by which this occurs are still unclear. This study employed an online cross-sectional survey of 267 Chinese students in Malaysia to explore the relationship between SNSs usage (usage engagement and acculturation usage) and life satisfaction by considering the mediating effect of host cultural identity and ethnic cultural identity. Data analysis relied on Statistical Package for the Social Sciences and AMOS software. The findings showed that SNSs usage engagement and two cultural identities helped to improve life satisfaction. Moreover, two cultural identities can explain how SNSs usage engagement influences life satisfaction. Contrary to expectations, acculturation usage had a non-significant influence on life satisfaction. However, under the mediating effect of host cultural identity, acculturation usage positively predicted life satisfaction. The research can provide references for the Malaysian government and educational institutions when introducing relevant policies to promote the life satisfaction of international students. The shortcomings and possibilities for future research are also discussed.